Sensory acceptability of sweet potatoes: Influence of the cultivar, cooking method and the city - Sosa, Miriam Patricia (2023)
This study aimed to evaluate the sensory acceptability of four sweet potatocultivars (Beauregard, Morada-INTA, Colorado-INTA, and Arapey), considering twocooking methods: boiled and baked; and two cities, 9 de Julio (9DJ) and San Pedro (SP),of Buenos Aires province. 120 women were recruited in each city. A home use test wascarried out. Each consumer received at home each sample in a bag containing threesweet potatoes and the evaluation form. The sensory acceptability of different characteristicsof the samples was evaluated, before and after cooking. To inquire the reasonsfor consumption of each sample, the methodology check all that apply (CATA) was used.Results: Of the two factors evaluated (city and cooking method), city had a significant influencewhen evaluating the samples. Participants of SP gave higher acceptability to Beauregardcultivar than 9DJ in most attributes. Colorado INTA had greater acceptability in somedescriptors by the consumers of 9DJ. While Arapey and Morada INTA had the greatestacceptability in 9DJ trial. In CATA results 9DJ consumers associated the Beauregard cultivarwith negative phrases: It tastes weird and It has little flavor/tasteless and to a lesser extent toThe internal color is artificial and It breaks when cooking. While SP consumers characterizedwith negative phrases the Arapey and Morada INTA samples as follows: It changes color(brown) quickly, Its shape is not regular and When cooked, it has threads or fibers.Conclusion: Consumer preferences provide opportunities for the development orimprovement of new cultivars. It would be interesting to extend this study to otherregions and/or countries.